Tradisi Si Semba (Adu Kaki) Masyarakat Toraja Di Lingkungan Kande Api, Kelurahan Buntu Barana’ Kecamatan Tikala - Hernawanti, Hernawanti; Manda, Darman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This study aims to determine the birth of the history of the si semba' tradition in Kande Api, the perception of the Kande Api community about the existence of external stigma related to the si semba' tradition which contains violence and how the community carries out the si semba' tradition in the midst of the co-19 pandemic. This research uses qualitative research methods with observation techniques, in-depth interviews, and in-depth analysis to obtain the desired data. The results of this study indicate that: the si semba' tradition was born from the habits of ancestors who used to only be carried out when there was a death party or rambu solo by the noble class. The tradition of si semba' which involves foot fighting does not mean violence at all but is a form of brotherhood and friendship values. The way to carry out the si semba' tradition during the covid-19 pandemic was to limit the participants who participated in the si semba' tradition.